Surat-surat pilihan 5: q.s al-‘adiyat (100), hadis tentang keutamaan shalat jamaah - Syamsudin, Wahhabi Farhan (Maliki Interdisciplinary Journal, 2026)
This article discusses the content of surah Al-‘Adiyat. it discusses hadiths regarding the virtues of congregational prayer, emphasizing its great rewards and the strong recommendation to perform it collectively. Thus, this paper integrates the study of tajwid and the practice of congregational prayer as a guide to improve the quality of Quranic recitation while deepening the understanding of the importance of prayer in daily life. The main message of this letter is the importance of balancing worldly life with awareness of the Day of Judgment. Besides enhancing spiritual values, congregational prayer also strengthens a sense of togetherness and solidarity among Muslims. However, in the modern era, congregational prayer has declined due to changes in lifestyle and technological advancements, necessitating collective awareness.